Efficacy and Cost-Efficacy of Biologic Therapies for Moderate to Severe Psoriasis: A Meta-Analysis and Cost-Efficacy Analysis Using the Intention-to-Treat Principle. (25th December 2013) - Chi, Ching-Chi; Wang, Shu-Hui
Abstract : Background . Compared to conventional therapies, biologics are more effective but expensive in treating psoriasis. Objective . To evaluate the efficacy and cost-efficacy of biologic therapies for psoriasis. Methods . We conducted a meta-analysis to calculate the efficacy of etanercept, adalimumab, infliximab, and ustekinumab for at least 75% reduction in the Psoriasis Area and Severity Index score (PASI 75) and Physician's Global Assessment clear/minimal (PGA 0/1). The cost-efficacy was assessed by calculating the incremental cost-effectiveness ratio (ICER) per subject achieving PASI 75 and PGA 0/1. Results . The incremental efficacy regarding PASI 75 was 55% (95% confidence interval (95% CI) 38%–72%), 63% (95% CI 59%–67%), 71% (95% CI 67%–76%), 67% (95% CI 62%–73%), and 72% (95% CI 68%–75%) for etanercept, adalimumab, infliximab, and ustekinumab 45 mg and 90 mg, respectively. The corresponding 6-month ICER regarding PASI 75 was $32, 643 (best case $24, 936; worst case $47, 246), $21, 315 (best case $20, 043; worst case $22, 760), $27, 782 (best case $25, 954; worst case $29, 440), $25, 055 (best case $22, 996; worst case $27, 075), and $46, 630 (best case $44, 765; worst case $49, 373), respectively. The results regarding PGA 0/1 were similar. Conclusions . Infliximab and ustekinumab 90 mg had the highest efficacy. Meanwhile, adalimumab had the best cost-efficacy, followed by ustekinumab 45 mg and infliximab.